The Perception of Muslim Converts on Religious Moderation and the Importance of Tolerance: A Study at the Mualaf Center Malang, Indonesia - Ermita Zakiyah; Novia Solichah; Nurul Shofiah; Abdul Fattah; Iqbal Ali Wafa (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2023)
This study aims to show how important it is to cultivate the values of moderation in a convert. This is important in order to anticipate the thoughts and attitudes of someone who has just become a Muslim towards the influence of intolerance and radicalism. Researchers used surveys with descriptive analysis techniques to measure the level of religious moderation. In this study, researchers also used qualitative methods with a phenomenological approach aimed at understanding the mindsets and perceptions of participants in diverse moderation. Participants in this study were five converts who were at least 3 years old and studying Islam. The perception of religious moderation among converts at the Muallaf Center Malang is shown through the views, attitudes, and practices of converts who accept the principles of nationhood. The results of the analysis showed that the level of religious moderation among converts in Muallaf Center Malang was in the high category. In addition, converts demonstrate conscious adherence to basic values, harmoniously integrating national aspirations into religious beliefs without contradicting state ideology. They showed a positive attitude towards national commitment, emphasized the importance of the ideals of Pancasila, respected the national flag, and implemented Pancasila in religious life. Their understanding of tolerance is prominent, as evidenced by their recognition of diversity, willingness to share facilities, and efforts to help non-Muslims. It all reflects a commitment to positive social contribution. Converts strongly oppose violence in religious conflicts, which means they are in line with the principles of religious moderation that reject violent extremism. Their adaptive approach to local culture, by embracing diverse practices, shows a willingness to acculturate while still maintaining religious beliefs.